Water and nutrition: a framework for action. - Chase, C.; Bahuguna, A.; Yue C.; Haque, S.; Schulte, M. (World Bank, 2019)
This framework for action was developed to support the inclusion of nutritional considerations in the design of water operations and to help formulate nutrition-enhancing water policy. Chronic undernutrition early in life can cause cognitive and physical impairments that prevent children from achieving their full potential and have lasting consequences on the human capital that is essential for economies of the future to be competitive. Water is at the core of healthy growth and development. It is a driver of better nutrition but, when poorly managed, can lead to negative impacts. The role of water for early child nutrition has centered on ensuring a hygienic living environment through clean water, adequate sanitation, and good hygiene. However, the importance of water for nutrition is much broader. A reliable water supply is needed to grow food to feed families, secure livelihoods, and provide income for other nutrition inputs. Yet water has become more variable as climate change accelerates, leading to more frequent and more damaging droughts and floods. Mismanagement of water resources results in shortages, pollution, and in some cases conflict, each of which impact a child’s ability to thrive. These relationships call for a more nuanced recognition of the role that water plays in early child nutrition, as well as the need for guidance on ways to mitigate the risks and boost the benefits of water investments for nutrition.